Analysis of Consumer Repurchase Intent on Organic Vegetable Products in the Modern Market - Indriyanti, Ima Yunita; Irianto, Heru; Kusnandar, Kusnandar (Ridwan Institute, 2024)
This research explores the commercial value of vegetables, especially in the context of consumers' need for sustainable vegetables, especially during the COVID-19 pandemic. The main focus is on organic vegetables, which are considered to have higher nutritional value and are free from harmful chemicals. Using the Theory of Planned Behavior approach, this study shows that attitudes, subjective norms, and perceptions of behavioral control influence the intention to repurchase organic vegetable consumers in Surakarta City. Other variables analyzed involve perceived value and customer satisfaction. This research method is quantitative associative, involving 130 respondents aged 20-60 years who have bought organic vegetable products in Surakarta City. Analysis of data utilizing Structural Equation Modeling (SEM) through smartPLS 3.0 revealed positive influences of attitudes, subjective norms, perceptions of behavioral control, and customer satisfaction on the intention to make repeat purchases. Perceived value and customer satisfaction also influence positive attitudes towards organic vegetables. However, the findings showed that perceived value did not have a positive influence on repurchase intent. Based on the results of the study, practical suggestions include increasing public information about the benefits of organic vegetables, expanding availability in markets or supermarkets, and actively promoting the health and environmental advantages of organic vegetable consumption. This effort is expected to strengthen consumer confidence and encourage the intention to repurchase organic vegetables in Surakarta City.